Composite hydrogel based on chitosan and acellular matrix and preparation method thereof
Through a composite hydrogel based on chitosan and decellularized matrix, the shortcomings of articular cartilage repair scaffold materials in the prior art are solved, cell aggregation and cartilage differentiation are achieved, cartilage repair is promoted, and excellent mechanical properties are provided. Porosity.
Patent Information
- Application Number
- CN202510018751.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to provide scaffolding materials suitable for cell aggregation and proliferation in articular cartilage repair, and collagen chitosan may lead to cartilage ossification, affecting the repair effect.
Using a composite hydrogel based on chitosan and decellular matrix, it is prepared by cross-linking of chitosan methacrylic acid and a methacrylic acid-modified decellular matrix to form a hydrogel with excellent mechanical properties and porosity, which promotes the Cell aggregation and cartilage differentiation.
It improves cell survival and cartilage differentiation ability, promotes cartilage repair, provides a microenvironment suitable for cell proliferation and differentiation, and has good injectability and mechanical properties.
Smart Images

Figure CN119424761A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and specifically relates to a composite hydrogel based on chitosan and acellular matrix, and a preparation method and application thereof. Background Art
[0002] Articular cartilage (AC) injury is a common orthopedic disease in clinical practice. Since articular cartilage lacks blood vessels, nerves and lymphatic vessels, its self-healing ability after injury is limited. Currently, cartilage transplantation is one of the treatment methods for articular cartilage repair. Tissue engineering provides a new idea for cartilage defect repair. Cells, growth factors and scaffold materials, as the three major elements of cartilage tissue engineering, play an important role in the process of cartilage regeneration.
[0003] At present, most studies on articular cartilage use scaffolds such as type I or type II collagen chitosan to repair cartilage defects. Since the use of collagen chitosan may cause cartilage ossification, it is not conducive to cartilage tissue repair. For example, Chinese patent CN101020083A discloses an integrated engineering scaffold of bone-cartilage composite tissue with a bionic functional interface, in which type II collagen and chitosan are used to prepare cartilage composite tissue. However, this method prepares a multi-layer bone-cartilage composite scaffold, which is not suitable for the adhesion growth and later proliferation and differentiation of mesenchymal stem cells. Therefore, it is urgent to develop a cartilage scaffold that can be suitable for cartilage repair, can be co-cultured with cells, has excellent mechanical properties and porosity, can be used in the research of tissue engineering cartilage, and provide a better choice for the treatment of cartilage defects. Summary of the invention
[0004] The invention provides a composite hydrogel based on chitosan and acellular matrix. The composite hydrogel can promote cell aggregation, improve cell survival and cartilage differentiation, and thus promote cartilage repair.
[0005] Specifically, the present invention provides a composite hydrogel based on chitosan and acellular matrix, wherein the composite hydrogel is prepared by cross-linking methacrylate chitosan and methacrylate modified acellular matrix; wherein the mass ratio of the methacrylate chitosan to the methacrylate modified acellular matrix is 2:1-5.
[0006] In some embodiments, the mass ratio of the methacrylate chitosan to the methacrylate modified decellularized matrix is 2:3-5. Preferably, the mass ratio of the methacrylate chitosan to the methacrylate modified decellularized matrix is 2:5.
[0007] In some embodiments, the concentration of the methacrylate chitosan is 2% (m / v), and the concentration of the methacrylate-modified decellularized matrix is 1-5% (m / v). Preferably, the concentration of the methacrylate chitosan is 2% (m / v), and the concentration of the methacrylate-modified decellularized matrix is 3-5% (m / v). More preferably, the concentration of the methacrylate chitosan is 2% (m / v), and the concentration of the methacrylate-modified decellularized matrix is 5% (m / v).
[0008] On the other hand, the present invention provides a method for preparing the above-mentioned composite hydrogel based on chitosan and decellularized matrix, the preparation method comprising the following steps: dissolving methacrylate chitosan and methacrylate modified decellularized matrix in deionized water, adding a photoinitiator, and irradiating with ultraviolet light to carry out a cross-linking reaction to obtain a composite hydrogel.
[0009] In some embodiments, the photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate.
[0010] In some embodiments, the ultraviolet irradiation time is 1-3 minutes.
[0011] In some embodiments, the method for preparing methacrylate chitosan comprises the following steps: dissolving chitosan in a solution, dropping methacrylic anhydride, stirring at 60°C-80°C for 2-5h to react, adjusting the pH to neutral with alkaline solution, and then stirring the mixed solution at 60°C-80°C for 20-30h, dialyzing the obtained product, and freeze-drying to obtain methacrylate chitosan.
[0012] In some embodiments, the mass volume ratio (g / mL) of the chitosan to the methacrylic anhydride is 2-5:5-10, preferably, the mass volume ratio is 3:8.
[0013] In some embodiments, the method for preparing methacrylate chitosan comprises the following steps: dissolving chitosan in acetic acid, dropping methacrylic anhydride, stirring at 60°C-70°C for 3 hours to react, adjusting the pH to neutral with sodium bicarbonate solution, and then stirring the mixed solution at 60°C-70°C for 24 hours, dialyzing the obtained product, and freeze-drying to obtain methacrylate chitosan.
[0014] In some embodiments, the preparation process of the methacrylic acid modified decellularized matrix comprises the following steps: dissolving the decellularized matrix in deionized water, adding methacrylic anhydride, adjusting the pH to 8.0-9.0, reacting at 4°C for 20-30h, dialyzing the obtained product, and freeze-drying to obtain the methacrylic acid modified decellularized matrix.
[0015] In some embodiments, the preparation process of the decellularized matrix comprises the following steps: A) Cut the cartilage into small pieces, freeze-thaw and immerse in 1% hydrogen peroxide for 1-2 hours, rinse with PBS solution and freeze in deionized water; B) Soak in 0.4%-0.8% trypsin and incubate at 37°C for 2-3 minutes to terminate digestion; C) The sample prepared in step B) was placed in PBS solution, 5%-8% Triton X-100 solution, 5%-8% sodium deoxycholate solution, 2%-4% Triton X-100 solution and PBS solution in sequence, 4% of each solution. o C constant temperature shaking for 24-36h, and each solution was washed with PBS and freeze-dried after treatment; D) The decellularized matrix is crushed again, digested with digestion solution, and then the reaction viscous solution is neutralized with alkali solution and 10×PBS, followed by dialysis and freeze-drying to prepare the decellularized matrix.
[0016] In some embodiments, in step A), the freeze-thaw cycle process includes: taking cartilage blocks, placing them in deionized water, freezing, and thawing; and then placing them in a 10% NaCl solution, freezing, and thawing.
[0017] In some embodiments, in step A), the cyclic freeze-thaw process includes: after cutting the meniscus, placing it in deionized water, freezing it at -80°C for 1-2 hours, and then thawing it at 37°C; then placing it in 10% NaCl solution, freezing it at -80°C for 1-2 hours, and then thawing it at 37°C.
[0018] In some embodiments, in step B), BSA is added to stop the digestion.
[0019] In some embodiments, in step B), the concentration of trypsin is 5%.
[0020] In some embodiments, in step C), the sample prepared in step B) is placed in PBS solution, 5% TritonX-100 solution, 6% sodium deoxycholate solution, 3% Triton X-100 solution and PBS solution, respectively, and stirred at 4°C for 36 h, 24 h, 24 h, 24 h, and 24 h, respectively. After treatment with each solution, the sample is washed with PBS and freeze-dried.
[0021] In some embodiments, in step D), the digestive fluid is an aqueous solution of HCl containing pepsin.
[0022] In some embodiments, in step D), the mass ratio of the decellularized matrix powder to pepsin is 5 to 20: 1. Preferably, the mass ratio is 10: 1.
[0023] In some embodiments, in step D), the decellularized matrix powder is crushed and placed in a 0.01 M HCL aqueous solution containing pepsin, stirred at room temperature for 72 hours, and the reaction viscous solution is neutralized with a NaOH aqueous solution and 10×PBS, dialyzed, and freeze-dried to prepare a decellularized matrix.
[0024] The present invention first carries out decellularized extracellular matrix treatment, adopts the mode of cyclic freezing and thawing to more fully lyse cells, and compared with non-freezing and thawing, the glycosaminoglycan component in the decellularized meniscus prepared is better retained. After being treated in 1% hydrogen peroxide, the permeability of cell membrane can be effectively destroyed. Afterwards, the sample is placed in PBS solution, Triton X-100 solution, sodium deoxycholate solution, Triton X-100 solution and PBS solution for treatment, and compared with untreated, cell debris and nuclear components are effectively removed, and the porosity of tissue is increased. The decellularized extracellular matrix immunogenic component clearance rate obtained by the above method is high, and a large amount of collagen and GAG are retained, with good biological activity. There is a nanofiber structure in the hydrogel micropores further prepared, which provides adhesion sites for cells, is conducive to stable cell adhesion and proliferation, and has a better promoting effect for tissue repair.
[0025] On the other hand, the present invention also provides the use of the composite hydrogel based on chitosan and decellularized matrix in the preparation of cartilage repair materials.
[0026] In some embodiments, the cartilage repair material is a cartilage repair scaffold.
[0027] In some embodiments, the cartilage is articular cartilage.
[0028] In some embodiments, the articular cartilage is mammalian knee cartilage.
[0029] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a photocurable injectable composite hydrogel with cell aggregation properties, which is composed of chitosan methacrylate (CSMA) and decellularized matrix modified with methacrylate (dECMMA), and can be used for cartilage defect repair. CSMA promotes cell aggregation by increasing the expression of cadherin, and cell aggregation is more conducive to improving their survival and cartilage differentiation compared with free cells, thereby promoting cartilage repair. dECMMA retains many inherent components and bioactive factors, providing a more natural microenvironment for cell proliferation and differentiation. By precisely adjusting the composition of CSMA and dECMMA, the physicochemical properties and biochemical functions can be expertly fine-tuned. The present invention investigates the effects of different CSMA and dECMMA composition ratios on hydrogel performance. Preferably, a composite hydrogel composed of 2% (m / v) CSMA and 1-5% (m / v) dECMMA, and more preferably, a composite hydrogel composed of 2% (m / v) CSMA and 5% (m / v) dECMMA has good injectability, good degradability, and high mechanical properties, and can regulate the aggregation of bone marrow mesenchymal stem cells (BMSCs). The bone marrow mesenchymal stem cell composite hydrogel transplantation cartilage defect model has a significant effect on repairing hyaline cartilage. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Characterization diagram of CSMA, dECM and dECMMA ( Figure 1 (a) is the H NMR spectrum and photograph of CSMA (showing the transition from sol to gel under ultraviolet irradiation), and the signal peaks of the methacrylamide group at 5.4 and 5.6 ppm are marked with yellow dotted rectangles; Figure 1 (b1) in the figure shows hematoxylin-eosin (H&E), toluidine blue, and Sirius red staining of dECM; Figure 1 (b2) Figure 1 (b3) in the figure shows the changes in the content of collagen and GAG in dECM; Figure 1 (c) is the H NMR spectrum and photograph of dECMMA (showing the transition from sol to gel under ultraviolet irradiation), and the signal peaks of the methacrylamide group at 5.4 and 5.6 ppm are marked with yellow dotted rectangles); Figure 2 The performance test results of CSMA / dECMMA composite hydrogel are shown in Figure ( Figure 2 (a) is the electron microscopy structure of CSMA / dECMMA hydrogel freeze-dried; Figure 2 (b) is the swelling rate curve of CSMA / dECMMA hydrogel; Figure 2 (c) is the equilibrium swelling diagram of CSMA / dECMMA hydrogel; Figure 2(d) is the compressive stress-strain curve of CSMA / dECMMA hydrogel; Figure 2 (e) is the shear stress scanning diagram of CSMA / dECMMA hydrogel; Figure 2 (f) is the time scan of CSMA / dECMMA hydrogel; Figure 2 (g) is the frequency scanning diagram of CSMA / dECMMA hydrogel; Figure 3 Figure 2 shows the results of in vitro cell compatibility experiments of CSMA / dECMMA composite hydrogels. Figure 3 (a) shows the live / dead staining of BMSCs after co-culture with CSMA / dECMMA hydrogel for 24 h and 48 h. Figure 3 (b) is the cell activity diagram of BMSCs after co-culture with CSMA / dECMMA hydrogel for 24 hours (OD value at 450nm wavelength); Figure 3 (c) is the cell activity diagram of BMSCs after co-culture with CSMA / dECMMA hydrogel for 48 hours (OD value at 450nm wavelength); Figure 3 (d) is a graph showing the changes in cell proliferation rate after BMSCs were co-cultured with CSMA / dECMMA hydrogel for 24 h and 48 h); Figure 4 The experimental results of the survival status and aggregation behavior of BMSCs cultured on CSMA / dECMMA composite hydrogels for 24 h and 48 h. Figure 4 (a) Figure 4 (b) in the figure shows live / dead staining and FITC-phalloidin staining respectively); Figure 5 This is the imaging experimental result of CSMA / dECMMA hydrogel promoting cartilage repair; Figure 6 Histological staining analysis of CSMA / dECMMA hydrogel promoting cartilage repair ( Figure 6 (a) Figure 6 (b) shows the histological analysis of the defect site using H&E staining and Safranin-O fast green staining, respectively). DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0032] Unless otherwise specified, the reagents or consumables used in the present invention are commercially available.
[0033] m / v means g / mL, for example 2% (m / v) means 2% g / mL.
[0034] Unless otherwise specified, % in this article refers to mass volume percentage.
[0035] Example 1 Preparation of composite hydrogel of chitosan and decellularized matrix Test materials TritonX-100, sodium deoxycholate, hematoxylin and eosin (H&E) staining kit, toluidine blue staining kit, Sirius red staining kit and FITC-phalloidin: Beijing Solarbio Technology Co., Ltd. Pepsin and chitosan: Shanghai Yuanye Biotechnology Co., Ltd. Hydroxyproline detection kit and glycosaminoglycan detection kit: Jiangsu Jingmei Biotechnology Co., Ltd. Methacrylic anhydride (94%, MA): Shanghai Aladdin Biochemical Technology Co., Ltd., China Alizarin red staining kit, Oil Red O staining kit, Alcian blue staining kit: Wuhan Punosai Life Science Technology Co., Ltd. Anti-CD34 rabbit antibody, anti-CD44 mouse antibody, anti-CD90 mouse antibody, coralite488-conjugated goat anti-rabbit IgG and coralite488-conjugated goat anti-mouse IgG: Proteintech, USA. Anti-Sox9 rabbit antibody, anti-Collage II mouse antibody, enzyme-labeled goat anti-mouse IgG, enzyme-labeled goat anti-rabbit IgG and 3,3′-diaminobenzidine substrate kit (DAB): Wuhan Saiweier Biotechnology Co., Ltd.
[0036] 1.1 Synthesis of chitosan methacrylate (CSMA): 3 g of chitosan was dissolved in acetic acid solution (1.5 wt%), 8 mL of methacrylic anhydride was added dropwise, and the mixture was stirred at 60 °C. o The mixture was stirred at 60 °C for 3 h. The acid solution was neutralized with sodium bicarbonate solution (10 wt%) to adjust the pH value to neutral. o C for 24 h. The obtained product was dialyzed with a dialysis bag for 4 days and then freeze-dried to obtain CSMA.
[0037] 1.2 Synthesis of methacrylic acid modified decellularized matrix (dECMMA): Cut the cartilage into small pieces, freeze them in deionized water for 2 hours, and freeze them at 37 o 37 °C, thawed, and then refrozen in 10% NaCl solution for 2 hours. oAfter freeze-thaw cycles, the cartilage fragments were immersed in 1% hydrogen peroxide for 1 h, washed with PBS, placed in deionized water, and frozen at -20°C for 48 h. The obtained samples were incubated in 0.5% trypsin at 37°C for 2.5 min, and BSA was added to terminate the digestion. They were then placed in PBS solution, 5% Triton X-100 solution, 6.0% sodium deoxycholate solution, 3% Triton X-100 solution, and PBS solution for 4 h. o C for 36 h, 24 h, 24 h, 24 h, and 24 h, respectively. After each solution treatment, the samples were washed with PBS. The samples were freeze-dried and stored. The freeze-dried samples were crushed into fine powder and placed in a 0.01M HCl aqueous solution containing pepsin, with a mass ratio of decellularized matrix fine powder to pepsin of 10:1. They were stirred at room temperature for 72 hours, and the reaction viscous solution was neutralized with NaOH aqueous solution and 10×PBS. The obtained product was dialyzed with a dialysis bag for 4 days and then freeze-dried in a freeze dryer to prepare a decellularized extracellular matrix (dECM).
[0038] Dissolve 1.2 g of the freeze-dried sample in deionized water, add 1.2 ml of methacrylic anhydride, adjust the pH to 8.0, and o The reaction was carried out under C conditions for 24 h. The obtained product was dialyzed with a dialysis bag and then freeze-dried to obtain dECMMA.
[0039] 1.3 Preparation of CSMA / dECMMA composite hydrogel: CSMA and dECMMA were dissolved in deionized water, and then lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP, 0.2%, m / v) was added. The mixed solution was exposed to ultraviolet light (405 nm, 20 mW.cm -2 ) for 1.5 minutes to obtain CSMA / dECMMA composite hydrogel. The CSMA concentration was maintained at 2% (m / v), and the final concentration of dECMMA was set to 0%, 1%, 3%, 5% and 7% (m / v), to obtain a series of composite hydrogels, named C 2 E 0 , C 2 E 1 , C 2 E 3 , C 2 E 5 and C 2 E 7 .
[0040] Example 2 Characterization of CSMA, dECM, and dECMMA 2.1 Characterization of CSMA: CSMA was characterized by NMR, where the chemical shifts in the H NMR spectrum of CSMA showed characteristic peaks at 5.4 and 5.6 ppm, which were attributed to the double bonds in the methacrylate group, proving that methacrylate was successfully modified onto the chitosan chain and that CSMA was successfully prepared. In addition, this modification enabled the prepared CSMA to exhibit good photosensitivity and rapid crosslinking under ultraviolet irradiation, such as Figure 1 As shown in (a) in .
[0041] 2.2 Characterization of dECM The decellularized tissue was fixed in 4% paraformaldehyde, embedded in paraffin, and serially sectioned at 5 μm for H&E staining, toluidine blue, and Sirius red staining. The results of H&E staining showed that all immunogenic components such as cells had been completely removed. Figure 1 As shown in (b1) in the figure. The results of toluidine blue staining showed that after decellularization, the glycosaminoglycan components in the meniscus were well preserved, such as Figure 1 As shown in (b1) in Figure 1, the results of Sirius red staining showed that after decellularization, the collagen (red area) in the meniscus was well preserved. Figure 1 As shown in (b1). Quantitative determination of collagen and GAG content showed that the content of collagen and GAG in dECM was lower than that in normal extracellular matrix, which was due to the loss during the decellularization process, as shown in Figure 1 (b2) and Figure 1 However, most of the collagen and GAGs are still retained in the dECM.
[0042] 2.3 Characterization of dECMMA By NMR characterization of dECMMA, compared with the unfunctionalized ECM, the chemical shifts in the NMR hydrogen spectrum of ECMMA showed characteristic peaks at 5.4 and 5.6 ppm, which were attributed to the double bonds in the methacrylate group, proving that methacrylate was successfully modified on the decellularized matrix chain and that dECMMA was successfully prepared. In addition, this modification made the prepared dECMMA show good photosensitivity and rapid cross-linking under ultraviolet irradiation, such as Figure 1 As shown in (c) in .
[0043] Example 3 Performance testing of CSMA / dECMMA composite hydrogel The structure of the hydrogel was observed by scanning electron microscopy. The results showed that the hydrogel prepared in Example 1 had a porous structure after freeze-drying, and the interconnected pores ranged from 100 to 200 μm. Figure 2 As shown in (a) in .
[0044] The water absorption and swelling rate of each group of scaffolds was determined by conventional weight method. The freeze-dried hydrogel was weighed and recorded as M1, then immersed in PBS buffer, and the sample was taken out at regular intervals, and the excess water on the surface was absorbed with gauze and weighed as M2. Each group of experiments was performed 3 times. The water absorption and swelling rate formula is as follows: Swelling rate = (M2-M1) / M1×100%. The swelling rate measurement results showed that the increase in dECMMA content reduced the swelling rate of the composite hydrogel. This is because the addition of dECMMA increases the cross-linking density, such as Figure 2 (b) and Figure 2 As shown in (c) in .
[0045] A universal universal testing machine was used to perform compression mechanical experiments. The samples were made into cylinders with a diameter of 9 mm and a thickness of 6 mm and placed on the stage. Each scaffold sample was preloaded with a vertical pressure of 0.01 N and subjected to compression tests at a strain rate of 5 mm / min. The stress-strain curve was plotted with deformation as the horizontal axis and pressure as the vertical axis. The results of the compression test showed that increasing the dECMMA content helped to improve the stiffness and toughness of the composite hydrogel ( Figure 2 (d) in the
[0046] The fixture was selected as a 40 mm flat plate, the plate spacing was set to 1 mm, and the test temperature was room temperature. The viscosity change of the hydrogel was tested by shear stress scanning, and the shear rate range was set from 0.1 to 100 s -1 . Then a time scan experiment was conducted under ultraviolet irradiation. The pre-gel solution was carefully placed on the rheometer plate, and the frequency was set to 10 rad / s and the strain was 1% until the storage modulus was reached. Finally, a frequency scan was performed to analyze the viscoelasticity of the hydrogel, from a low frequency of 0.1 rad / s to a high frequency of 100 rad / s, with a constant strain of 1%.
[0047] The shear stress scanning results show that the viscosity of all solutions decreases with the increase of shear rate, and they have certain injectability ( Figure 2 (e) in the figure). The time scan results show that the composite hydrogel precursor solution is transformed into a gel state after ultraviolet irradiation ( Figure 2 (f) in the figure. The frequency scanning results show that the presence of dECMMA enhances the stability of the gel ( Figure 2 (g) in.
[0048] Example 4: In vitro cytocompatibility experiment of CSMA / dECMMA composite hydrogel Cell culture: Rabbit bone marrow mesenchymal stem cells (BMSCs) were cultured in RPMI modified medium supplemented with 10% fetal bovine serum for mesenchymal stem cells and 1% penicillin-streptomycin solution. The culture environment was 37 oC, 5% CO 2 .
[0049] Cytocompatibility: Live / dead staining and CCK-8 assay were used to detect the toxicity of the composite hydrogel to BMSCs.
[0050] (1) Live / dead staining: a density of 3 × 10 4 BMSCs of 100 cells / mL were inoculated on a 24-well plate, and 1 ml of RPMI 1640 culture medium with a volume ratio of 10% fetal bovine serum and 1% penicillin-streptomycin was added to each well for 24 hours. Then, the sterilized hydrogel samples of different components were placed in the culture medium, and after incubation for 24 hours and 48 hours, the live / dead staining kit reagent was added to detect the distribution and quantity comparison of the number of live cells and dead cells.
[0051] (2) CCK8 method: The density is 2 × 10 4 BMSCs of 100 cells / mL were inoculated on a 24-well plate, and 1 ml of RPMI 1640 culture medium with a volume ratio of 10% fetal bovine serum and 1% penicillin-streptomycin was added to each well for 24 hours. Then, the sterilized hydrogel samples of different components were placed in the culture medium, and after incubation for 24 hours and 48 hours, CCK8 reagent was added, and the absorbance value (OD 450) at a wavelength of 450 nm was measured using an enzyme-linked immunosorbent assay.
[0052] The results showed that after 24 and 48 h of co-culture with the composite hydrogel, most of the bone marrow mesenchymal stem cells were alive (green cytoskeleton, no red nucleus), e.g. Figure 3 In addition, the CCK-8 assay results showed that after 24 and 48 hours of co-culture with the composite hydrogel, the proliferation of cells was not significantly different from that of the control cells, as shown in Figure 2. Figure 3 (b) Figure 3 (c) Figure 3 These results confirm that the prepared composite hydrogel has good cell compatibility.
[0053] Example 5 Experiment on regulating cell aggregation behavior of CSMA / dECMMA composite hydrogel in vitro In order to observe the aggregation behavior of BMSCs on the composite hydrogel, a density of 3×10 4 BMSCs with a density of 100 cells / mL were seeded on sterilized composite hydrogels in 24-well plates. BMSCs were stained with Calcein-AM / PI dye and FITC-phalloidin and observed under laser confocal microscope after incubation for 24h and 48h.
[0054] The results showed that at 24 h and 48 h after sowing, the2 E 0 and C 2 E 1 BMSCs on the composite hydrogel are in an aggregated state. 2 E 3 and C 2 E 5 The BMSCs on the composite hydrogels were in an aggregated and spread state, while C 2 E 7 The BMSCs on the composite hydrogel were in a dispersed spreading state. Calcein-AM / PI staining results showed that the cells in the aggregates were still active. Figure 4 As shown in (a) in the figure, further cytoskeleton staining showed that the adhesion area of cell aggregation increased significantly with the extension of culture time, as shown in Figure 4 As shown in (b) in .
[0055] It is worth noting that the aggregated state of stem cells has certain advantages over the single spread state: (1) higher cell viability; (2) maintenance of stemness; (3) enhanced chondrogenic differentiation ability. 2 E 0 , C 2 E 1 , C 2 E 3 and C 2 E 5 Composite hydrogel ratio C 2 E 7 Composite hydrogels are more conducive to cartilage repair. In addition, considering that cartilage is a load-bearing tissue, a repair material with certain mechanical properties and good injectability is needed to fill the defect. Combined with the above research on the injectability, microstructure, mechanical properties and other properties of hydrogels, C is preferred. 2 E 1 , C 2 E 3、 C 2 E 5 Composite hydrogel, more preferably, select C 2 E 5 The composite hydrogel was used as a scaffold material for encapsulating BMSCs and its ability to promote cartilage repair in vivo was further evaluated.
[0056] Example 6 Study on the ability of CSMA / dECMMA composite hydrogel to promote cartilage repair (1) Tissue imaging analysis The experimental animals used were New Zealand white rabbits (male, 5-6 months old), weighing about 3 kg. After preoperative anesthesia, the rabbits were placed with their abdomen facing upwards, and the upper limbs and left lower limb were fixed. The hair around the knee joint was shaved, disinfected with iodine tincture, the joint capsule was cut along the medial side of the joint, and a cartilage injury notch was drilled in the concave part of the femoral condyle. The rabbits were randomly divided into three groups: (A) blank control group, (B) injected with C 2 E 0 Hydrogel group, (C) injection of C 2 E 5 Hydrogel group. Hydrogel was injected into the wound and cured by ultraviolet light. Four rabbits in each group were randomly killed 4 weeks after implantation; the remaining rabbits were killed 8 weeks after implantation. Tissues were obtained for imaging and histological analysis.
[0057] Cartilage was collected at 4 and 8 weeks after surgery to evaluate the long-term repair effect of the hydrogel in vivo. Figure 5 As shown in the figure, at the macroscopic level, the new tissue in the control group was thinner at 4 weeks, with a clear boundary with the surrounding tissue, and the defect site was still clearly visible. 2 E 0 The injured part of the C group was filled with regenerated new tissue with an uneven surface, showing a better repair effect than the control group. 2 E 5 The new tissue regenerated relatively complete and smooth, and was well integrated with the surrounding tissue. We further evaluated the growth of subchondral bone by Micro-CT, and the results showed that there was still a certain defect in the center of the subchondral bone in the three groups. Among them, the area of cartilage defect in the control group was the largest, followed by the C 2 E 0 Group, C 2 E 5 At 8 weeks after surgery, the cartilage lesions in the control group showed insufficient filling of regenerated cartilage tissue. 2 E 0 In the cartilage injury group, the new cartilage tissue basically filled the defect, but the color was milky white, and there was a clear boundary between it and the normal cartilage. 2 E 5 The cartilage injury in group C was basically filled with new tissue, with a smooth surface and uniform color, and well integrated with the surrounding normal cartilage. Micro-CT three-dimensional reconstruction, cross-sectional and coronal images showed that only C 2 E 5 The group formed a completely closed subchondral bone, C 2 E 0 The new bone formation in the control group was insufficient, and the regenerated subchondral bone in the control group had not yet closed, with obvious gaps in the defect area.
[0058] (2) Histological staining analysis In order to further evaluate the in vivo cartilage repair effect of the composite hydrogel, we sectioned the collected specimens and performed corresponding histological staining: H&E staining and Safranin-O fast green staining to evaluate the ability of the composite hydrogel to promote cartilage damage repair at the tissue microscopic level ( Figure 6 ). At 4 weeks after surgery, H&E staining results showed that continuous tissue covered the defect surface in the cartilage injury area of each group, with a clear boundary between the new tissue and the surrounding normal cartilage tissue, and a certain degree of subchondral bone defect. 2 E 0 The defect in group C was mainly filled with fibrocartilage tissue, while 2 E 5 The injured part of the group was mainly filled with hyaline cartilage. Then we performed safranin O-fast green staining to observe the repair of cartilage. The basic dye safranin O combined with basophilic cartilage to show red, and the acidic dye fast green combined with eosinophilic bone to show green. At the 4th week, all groups showed different degrees of positive safranin O staining, indicating that cartilage matrix began to deposit on the defect surface. Among them, C 2 E 5 Compared with other tissues, the staining of the control group covered a larger area and generated new cartilage faster. At 8 weeks after surgery, HE staining results showed that the cartilage in the control group still had a large defect. 2 E 0 Obvious cracks were observed in the new tissues of group C. 2 E 5 The group showed the best repair effect, including a relatively smooth cartilage surface, good integration with the host cartilage tissue, and a structure similar to natural tissue. Safranin-O fast green staining results showed that the defect area of the control group was basically non-red due to the lack of new cartilage formation. 2 E 0 The defect site of group C had a large area of positive red-stained tissue, showing cartilage hyperplasia. 2 E 5 The staining results of the group were closest to the natural cartilage, and the cartilage regeneration was more complete and uniform.
[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.
Claims
1. A composite hydrogel based on chitosan and acellular matrix, characterized in that: The composite hydrogel is prepared by cross-linking methacrylate chitosan and methacrylate modified decellularized matrix; wherein the mass ratio of the methacrylate chitosan to the methacrylate modified decellularized matrix is 2:1-5.
2. The composite hydrogel based on chitosan and decellularized matrix according to claim 1, characterized in that: The mass ratio of the methacrylic acid chitosan to the methacrylic acid modified decellularized matrix is 2:3-5.
3. The composite hydrogel based on chitosan and decellularized matrix according to claim 1, characterized in that: The composite hydrogel preparation method comprises the following steps: dissolving methacrylic acid chitosan and methacrylic acid modified decellularized matrix in deionized water, adding a photoinitiator, and irradiating with ultraviolet rays to carry out a crosslinking reaction to obtain the composite hydrogel.
4. The composite hydrogel based on chitosan and decellularized matrix according to claim 3, characterized in that: The photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate.
5. The composite hydrogel based on chitosan and decellularized matrix according to claim 3, characterized in that: The UV irradiation time is 1-3 minutes.
6. The composite hydrogel based on chitosan and decellularized matrix according to claim 3, characterized in that: The preparation method of methacrylate chitosan comprises the following steps: dissolving chitosan in a solution, dropping methacrylic anhydride, stirring at 60-80°C for 2-5h to react, adjusting the pH to neutral with alkali solution, stirring the mixed solution at 60-80°C for 20-30h, dialyzing the obtained product, and freeze-drying to obtain methacrylate chitosan.
7. The composite hydrogel based on chitosan and decellularized matrix according to claim 6, characterized in that: The mass volume ratio (g / mL) of the chitosan to the methacrylic anhydride is 2-5:5-10.
8. The composite hydrogel based on chitosan and decellularized matrix according to claim 3, characterized in that: The preparation process of the methacrylic acid modified decellularized matrix comprises the following steps: dissolving the decellularized matrix in deionized water, adding methacrylic anhydride, adjusting the pH to 8.0-9.0, reacting at 4°C for 20-30h, dialyzing the obtained product, and freeze-drying to obtain the methacrylic acid modified decellularized matrix.
9. Use of a composite hydrogel based on chitosan and acellular matrix according to any one of claims 1 to 8 in the preparation of a cartilage repair material.
10. The use according to claim 9, characterized in that: The cartilage is articular cartilage.
Citation Information
Patent Citations
Integral engineering rack of interface osteochondro tissue with bionic function
CN101020083A
Crosslinking method for improving biocompatibility of acellular matrix
CN109833119A
Antibacterial composite hydrogel as well as preparation method and application thereof
CN112778772A
Sturgeon cartilage acellular matrix sericin biological ink and preparation method thereof
CN115444983A
Hydrogel based on cartilage matrix and preparation method and application thereof
CN116808305A
Cited By
In-situ gelling type tissue repair composite material as well as preparation method and application thereof
CN121891616A